Transposon-mediated Generation of Cellular and Mouse Models of Splicing Mutations to Assess the Efficacy of snRNA-based Therapeutics - Elena Barbon; Mattia Ferrarese; Laetitia van Wittenberghe; Peggy Sanatine; Giuseppe Ronzitti; Fanny Collaud; Pasqualina Colella; Mirko Pinotti; Federico Mingozzi (Elsevier, 2016)
Disease-causing splicing mutations can be rescued by variants of the U1 small nuclear RNA (U1snRNAs). However, the evaluation of the efficacy and safety of modified U1snRNAs as therapeutic tools is limited by the availability of cellular and animal models specific for a given mutation. Hence, we exploited the hyperactive Sleeping Beauty transposon system (SB100X) to integrate human factor IX (hFIX) minigenes into genomic DNA in vitro and in vivo. We generated stable HEK293 cell lines and C57BL/6 mice harboring splicing-competent hFIX minigenes either wild type (SChFIX-wt) or mutated (SChFIXex5-2C). In both models the SChFIXex5-2C variant, found in patients affected by Hemophilia B, displayed an aberrant splicing pattern characterized by exon 5 skipping. This allowed us to test, for the first time in a genomic DNA context, the efficacy of the snRNA U1-fix9, delivered with an adeno-associated virus (AAV) vector. With this approach, we showed rescue of the correct splicing pattern of hFIX mRNA, leading to hFIX protein expression. These data validate the SB100X as a versatile tool to quickly generate models of human genetic mutations, to study their effect in a stable DNA context and to assess mutation-targeted therapeutic strategies.